SMARCA4-Deficient Carcinoma of Uterine Cervix Resembling SCCOHT-Case Report - Sirák, Igor; Laco, Jan; Vošmiková, Hana; Mell, Loren K; Herrera, Fernanda G; Šenkeříková, Mária; Vošmik, Milan (Pathology oncology research, 2021)
Small cell carcinoma of hypercalcemic type (SCCOHT) is a rare gynaecological neoplasm, originating mostly in the ovaries. Cervical origin of this very aggressive malignancy with unknown histogenesis is an extremely rare condition, without published management recommendations. Alterations in SMARCA4 gene are supposed to play the major role in SCCOHT oncogenesis and their identification is crucial for the diagnosis. Adequate genetic counselling of the patients and their families seems to be of great importance. Optimal management and treatment approaches are not known yet but may extremely influence the prognosis of young female patients that suffer from this very resistant disease. Nowadays, a translational research seems to be the key for the further diagnostic and treatment strategies of SCCOHT. The purpose of the case report is to provide practical information and useful recommendations on the diagnosis, management, and treatment of SMARCA4-deficient carcinoma of the uterine cervix resembling SCCOHT.
Keywords: cervical cancer; jaderné proteiny; high-risk; hyperkalcemie; DNA Helicases; Hypercalcemia; Nuclear Proteins; gynecological cancer; personalized treatment; predictive marker; mladiství; diagnostic biomarker; mutace; DNA-helikasy; Transcription Factors; nádory děložního čípku; Fatal Outcome; Biomarkers, Tumor; case report; malobuněčný karcinom; transkripční faktory; ženské pohlaví; nádorové biomarkery; Mutation; Humans; Uterine Cervical Neoplasms; Female; Carcinoma, Small Cell; Adolescent; fatální výsledek; lidé